Outcome and durability of mitral valve annuloplasty in atrial secondary mitral regurgitation. Issue 18 (15th June 2021) - Deferm, Sébastien; Bertrand, Philippe B; Verhaert, David; Dauw, Jeroen; Van Keer, Jan M; Van De Bruaene, Alexander; Herregods, Marie-Christine; Meuris, Bart; Verbrugghe, Peter; Rex, Steffen; Vandervoort, Pieter M; Rega, Filip
Abstract : Objectives: Atrial secondary mitral regurgitation (ASMR) is a clinically distinct form of Carpentier type I mitral regurgitation (MR), rooted in excessive atrial and mitral annular dilation in the absence of left ventricular dysfunction. Mitral valve annuloplasty (MVA) is expected to provide a more durable solution for ASMR than for ventricular secondary MR (VSMR). Yet data on MR recurrence and outcome after MVA for ASMR are scarce. This study sought to investigate surgical outcomes and repair durability in patients with ASMR, as compared with a contemporary group of patients with VSMR. Methods: Clinical and echocardiographic data from consecutive patients who underwent MVA to treat ASMR or VSMR in an academic centre were retrospectively analysed. Patient characteristics, operative outcomes, time to recurrence of ≥moderate MR and all-cause mortality were compared between patients with ASMR versus VSMR. Results: Of the 216 patients analysed, 97 had ASMR opposed to 119 with VSMR and subvalvular leaflet tethering. Patients with ASMR were typically female (68.0% vs 33.6% in VSMR, p<0.001), with a history of atrial fibrillation (76.3% vs 33.6% in VSMR, p<0.001), paralleling a larger left atrial size (p<0.033). At a median follow-up of 3.3 (IQR 1.0–7.3) years, recurrence of ≥moderate MR was significantly lower in ASMR versus VSMR (7% vs 25% at 2 years, overall log-rank p=0.001), also when accounting for all-cause death as competing risk (subdistribution HR 0.50 in ASMR, 95% CI 0.29 to 0.88, p=0.016). Moreover, ASMR was associated with better overall survival compared with VSMR (adjusted HR 0.43 95% CI 0.22 to 0.82, p=0.011), independent from baseline European System for Cardiac Operative Risk Evaluation II surgical risk score. Conclusion: Prognosis following MVA to treat ASMR is better, compared with VSMR as reflected by lower all-cause mortality and MR recurrence. Early distinction of secondary MR towards underlying ventricular versus atrial disease has important therapeutic implications.